Valores de proteína, energia e aminoácidos digestíveis da farinha de carne e ossos para a tilápia do Nilo - Xavier, Tadeu Orlandi (2011)
This work was carried out to determine values of energy, protein and digestible amino acids from meat and bones meals with different crude protein levels. An in vivo digestibility trial was conducted with 180 juveniles of Nile tilapia (32.65 ± 4.52 g) GIFT strain, divided into conical tanks. Five meat and bones meals with 30.90, 35.26, 38.06, 41.38 and 44.36% crude protein were evaluated. To determine the apparent digestibility coefficients (ADC) was elaborated a reference diet based on soybean meal and poultry meal byproduct with approximately 3,120 kcal DE/kg and 32% of crude protein. The diets were composed of 70% of reference diet and 30% of each meat and bones evaluated. A completely randomized design with five treatments and three replications was used. The values of digestibility of gross energy, crude protein and amino acids and energy values, protein and digestible amino acids were subjected to linear or quadratic regression. It was observed a linear increase on the crude protein and digestible energy with , the increased levels of crude protein of meal. The average apparent digestibility of essential amino acids (including cystine and tyrosine) of meat and bones meals with 30.90, 35.26, 38.06, 41.38 and 44.36% crude protein were 82.21, 86.50, 90.06, 89.94 and 92.61% respectively. A great variation between the ADC of crude protein, gross energy and amino acids between and among each meat and bone meals was observed. Based on the ideal protein concept, the most limiting amino acids in meat and bone meal are, respectively: sulfur amino acids, threonine and isoleucine.